1983
DOI: 10.1093/oxfordjournals.aje.a113677
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Among Mexican Americans in Starr County, Texas

Abstract: An increasing body of evidence suggests that diabetes mellitus constitutes a major health burden among the Mexican-American population. For example, county-wide death rates in Texas attributable to diabetes from 1970-1981 range from 2.5-52.0 diabetes deaths per 1000 total deaths with the highest rates generally occurring in counties whose populations are more than 75% Spanish ancestry. To assess the prevalence and morbidity of noninsulin-dependent diabetes mellitus among Mexican Americans, 14% of the Starr Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
88
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 151 publications
(92 citation statements)
references
References 0 publications
3
88
1
Order By: Relevance
“…In some areas of the Lower Rio Grande Valley, type 2 diabetes affects 50% of the Hispanic population Ͼ35 years of age (2). Mexican Americans tend to be diagnosed with diabetes at younger ages and exhibit higher fasting glucose levels, decreased insulin sensitivity, increased insulin response, and more severe forms of diabetes complications (3)(4)(5).…”
mentioning
confidence: 99%
“…In some areas of the Lower Rio Grande Valley, type 2 diabetes affects 50% of the Hispanic population Ͼ35 years of age (2). Mexican Americans tend to be diagnosed with diabetes at younger ages and exhibit higher fasting glucose levels, decreased insulin sensitivity, increased insulin response, and more severe forms of diabetes complications (3)(4)(5).…”
mentioning
confidence: 99%
“…8 In addition, 50% of Mexican-American adults 35 y or older either have diabetes themselves or have a first-degree relative with diabetes. 10 Modest weight loss can have a beneficial effect on cardiovascular disease and diabetes risk factors. 1,[11][12][13][14] It is likely that Mexican Americans, and other minority groups, would also experience these same benefits with modest weight loss.…”
mentioning
confidence: 99%
“…
Numerous studies have shown that Mexican Americans have an increased prevalence [1][2][3][4] and incidence [5] of non-insulin-dependent diabetes mellitus (NIDDM) relative to non-Hispanic whites. The Mexican American population is characterized by increased adiposity [1][2][3][4]6], a more centralized distribution of body fat [6,7], hyperinsulinaemia [8][9][10] and insulin resistance [11,12].

Metabolic factors have been shown to be important risk factors for the development of NIDDM.

…”
mentioning
confidence: 99%
“…The Mexican American population is characterized by increased adiposity [1][2][3][4]6], a more centralized distribution of body fat [6,7], hyperinsulinaemia [8][9][10] and insulin resistance [11,12].Metabolic factors have been shown to be important risk factors for the development of NIDDM. Both insulin resistance [13,14] and hyperinsulinaemia [13,[15][16][17][18][19] have been shown to predict NIDDM.…”
mentioning
confidence: 99%
See 1 more Smart Citation